2020
DOI: 10.1177/1758835920946156
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of afatinib in patients with lung adenocarcinoma harboring complex epidermal growth factor receptor mutation

Abstract: Background and aims: Epidermal growth factor receptor tyrosine kinase inhibitors (EGFR TKIs) are effective against classical EGFR mutations in lung cancer. However, their effectiveness and the prognosis of lung cancer patients with complex EGFR mutations are not well delineated. Therefore, we aimed to investigate the treatment effectiveness of different EGFR TKIs in patients with complex EGFR mutations. Patients and methods: From 2005 to 2020, we collected lung adenocarcinoma tissue samples for EGFR mutation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 69 publications
(101 reference statements)
3
26
0
Order By: Relevance
“…In a retrospective study focusing on compound mutations, 125 NSCLC patients with these alterations, excluding de novo exon 20 p.T790M compounds, received an EGFR TKI as first-line treatment [ 47 ]. Overall, treatment with afatinib showed longer PFS than gefitinib and erlotinib, and longer OS than erlotinib.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective study focusing on compound mutations, 125 NSCLC patients with these alterations, excluding de novo exon 20 p.T790M compounds, received an EGFR TKI as first-line treatment [ 47 ]. Overall, treatment with afatinib showed longer PFS than gefitinib and erlotinib, and longer OS than erlotinib.…”
Section: Resultsmentioning
confidence: 99%
“…In cases of compound common EGFR mutations, no difference was observed among the three drugs in terms of response (RR: gefitinib 83%, erlotinib 73.7%, afatinib 88.2%) and PFS (gefitinib 10.9, erlotinib 8.5, afatinib 9.6 months, p = 0.385). Conversely, afatinib demonstrated higher RR and prolonged PFS in those patients with combined uncommon pattern (RR: afatinib 78.9%, gefitinib 38.9%, erlotinib 20%, p = 0.013; PFS: afatinib 10.5, gefitinib 3, erlotinib 0.9 months) [ 47 ] ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…In both cases, K757N was found in combination with the classical EGFR sensitizing mutation L858R. In the case report by Wu et al [7], the patient had a transient, stable response to TKI therapy with gefitinib for 8.8 months before progression. The other reported case also received gefitinib for 12.4 months before progression [8].…”
Section: Discussion/conclusionmentioning
confidence: 94%
“…In line with our observation, a pooled analysis revealed that afatinib resulted in an objective response rate (ORR) of 77.1% and a median time to treatment failure (TTF) of 14.7 mo [95% confidence interval (CI): 6.8-18.5 mo] in EGFR TKI–naive patients harboring compound mutations[ 6 ]. A recent retrospective study also shows that afatinib is associated with a more favorable PFS compared with gefitinib [hazard ratio (HR) = 2.01; 95%CI: 1.11-3.62] and erlotinib [HR = 2.61; 95%CI: 1.31-5.22] in patients with EGFR compound mutations[ 7 ]. Especially in those with uncommon patterns (without 19 deletion and L858R), afatinib yielded a higher response rate (afatinib vs gefitinib vs erlotinib: 78.9% vs 38.9% vs 20.0%, P = 0.013) and significantly longer PFS (afatinib vs gefitinib vs erlotinib: 10.5 mo vs 3.0 mo vs 0.9 mo).…”
Section: Discussionmentioning
confidence: 99%